1988
DOI: 10.1007/bf01314654
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus infection of the human sensory neuron

Abstract: Herpes simplex virus (HSV) type 1 was used to infect cultures of human embryonic dorsal root ganglion cells. Infected cultured were studied by electron microscopy. Viral nucleocapsids were observed to be internalized into neuronal cells bodies and neuritic extensions by fusion of the viral envelope and the plasma membrane. No signs of internalization by endocytosis were noted. Nucleocapsids were transported in neurites and were within 2 hrs postinfection found located near the microtubules and close to the nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
116
2

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(128 citation statements)
references
References 34 publications
(25 reference statements)
10
116
2
Order By: Relevance
“…For example, some neurotropic viral pathogens, such as poliovirus, enter axons by endocytosis and subsequently traverse the axon in the endosome (25). However, by transmission electron microscopy (TEM), herpesvirus capsids are typically observed directly in the cytosol subsequent to entry into axons (15,26,27). Similarly, we see membrane-free capsids in axons in our culture model by TEM (data not shown).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…For example, some neurotropic viral pathogens, such as poliovirus, enter axons by endocytosis and subsequently traverse the axon in the endosome (25). However, by transmission electron microscopy (TEM), herpesvirus capsids are typically observed directly in the cytosol subsequent to entry into axons (15,26,27). Similarly, we see membrane-free capsids in axons in our culture model by TEM (data not shown).…”
Section: Discussionmentioning
confidence: 78%
“…Although transmission electron microscopy studies of herpesviruses infections in sensory neurons support a model of viral entry by fusion at the host cell plasma membrane, endocytosis of virions can result in productive infections in some cell types (15,16). To determine whether axonal transport of capsids was associated with endosome transport, sensory neurons and nonneuronal cells present in the disassociated neural culture were together infected with the GFP-capsid virus after labeling of the endocytic pathway with a TMR-dextran fluid-phase marker.…”
Section: Capsids and Endosomes Traffic Independently In Axonsmentioning
confidence: 99%
“…Within neurons, HSV-1 nucleocapsid and tegument proteins travel in a retrograde manner to the neuronal cell body where the viral genome is released into the nucleus. [96][97][98] The transport of alphaherpesvirus nucleocapsids along axons has been estimated to occur at rates of 0.5-3.5 mm/s, 99 suggesting that transport is an active process. While the exact mechanism of HSV transport along axons has yet to be elucidated, recent studies have identified viral and host cell components that contribute to this process.…”
Section: Virus Attachment and Entrymentioning
confidence: 99%
“…Binding to the cell, and fusion of the viral envelope and the plasma membrane of the cell by which penetration is accomplished (Fuller & Spear, 1987;Lycke et al, 1988;Morgan et al, 1968), includes activities of glycoproteins B, C, D and H (Cai et al, 1988;Campadelli-Fiume et al, 1990;Desai et al, 1988;Kfihn et al, 1990;Ligas & Johnsson, 1988;Muggeridge et al, 1990), but it has not been established whether and how the glycoproteins interact and whether nonglycosylated envelope proteins are involved also in the attachment of the virion to the plasma membrane (Langeland et al, 1990;Spear, 1985).…”
Section: Discussionmentioning
confidence: 99%